Platelets in Rheumatoid Arthritis - Pazdur, J; Kopeć, Maria (Thrombosis and Haemostasis, 1970)
Platelet counts and adhesiveness in vivo were examined in 140 patients with rheumatoid arthritis and in 30 healthy subjects. Increased platelet counts were found in 50% of cases and impaired adhesiveness in vivo in 40%. Thrombocyte counts showed high positive correlation with leukocytosis but none with adhesiveness in vivo and degree of anemia. Ivy bleeding time was prolonged in 15 among 30 examined r.a. cases. Adhesion of normal platelets to purified collagen prepared from tendons of r.a. patients was found to be unimpaired. Aggregation of platelets with connective tissue extracts was delayed in r.a. PRP as compared with normal PRP. Extracts of r.a. synovia was less effective as aggregating agent than extracts of control synovia. It was found that a single dose of aspirin (2 g) does not influence platelet adhesiveness in vivo in healthy persons. On the basis of the presented results and literature data it is suggested that overproduction of platelets is a probable cause of thrombocytosis in r. a. while impairment of in vivo adhesiveness may be due to intrinsic defect of platelet and/or to presence of some inhibitory substances in blood and tissues.